2017
DOI: 10.5296/ijafr.v7i2.11782
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Generic Skills in Accounting Education: Evidence from Egypt

Abstract: Nowadays, globalization, new economic challenges and innovations in information technologies (IT) influenced the role and domain of professional accountants. The current accreditation requirements and educational frameworks of the contemporary accounting profession emphasize the importance of broad 'generic skills'. This research aims to fill the gap in studying generic skills in Egypt by examining the importance of generic skills in accounting education. The research results are consistent with the Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Oral communication appeared to be consistently desired across all three job levels. The findings are consistent with those of (Hussein, 2017), who identified communication skills as one of the five factors of importance for accounting graduates. It was interesting to note that critical thinking seemed to be preferred more as levels increased (54% at entry, 68.2% supervisory, 76.9% upper).…”
Section: Supervisorysupporting
confidence: 90%
“…Oral communication appeared to be consistently desired across all three job levels. The findings are consistent with those of (Hussein, 2017), who identified communication skills as one of the five factors of importance for accounting graduates. It was interesting to note that critical thinking seemed to be preferred more as levels increased (54% at entry, 68.2% supervisory, 76.9% upper).…”
Section: Supervisorysupporting
confidence: 90%
“…Additionally, the Initial Test of Competence was taken in January and June 2018, and UKZN students did incredibly well on both occasions, demonstrating the relationship's success. According to Hussein's (2017) research in Egypt, university students' professional skills are crucial. The author suggested that Egyptian colleges review their approach to teaching accounting in order to forge solid ties with professional firms.…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary business environment demands accountants to possess a blend of technical accounting skills and soft skills such as critical thinking, communication, and adaptability. The integration of generic skills in accounting education is crucial to prepare accountants for the multifaceted challenges of the modern business world (Hussein, 2017).…”
Section: Accounting Challenges In the Digital Eramentioning
confidence: 99%